2014
DOI: 10.1038/tp.2014.51
|View full text |Cite
|
Sign up to set email alerts
|

Women with the Alzheimer’s risk marker ApoE4 lose Aβ-specific CD4+ T cells 10–20 years before men

Abstract: Adaptive immunity to self-antigens causes autoimmune disorders, such as multiple sclerosis, psoriasis and type 1 diabetes; paradoxically, T- and B-cell responses to amyloid-β (Aβ) reduce Alzheimer's disease (AD)-associated pathology and cognitive impairment in mouse models of the disease. The manipulation of adaptive immunity has been a promising therapeutic approach for the treatment of AD, although vaccine and anti-Aβ antibody approaches have proven difficult in patients, thus far. CD4+ T cells have a centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…) and there is an age‐ and APOE ‐dependent decrease in Aβ‐specific CD4 + T‐cell activity in humans (Begum et al . ). Indeed, Aβ‐specific CD4 + T‐cell activity follows the order: APOE4 ‐negative males > APOE4‐ positive males > APOE4 ‐negative females > APOE4‐ positive females (Begum et al .…”
Section: Apoe‐modulated Inflammation: Current Perspectivementioning
confidence: 97%
See 3 more Smart Citations
“…) and there is an age‐ and APOE ‐dependent decrease in Aβ‐specific CD4 + T‐cell activity in humans (Begum et al . ). Indeed, Aβ‐specific CD4 + T‐cell activity follows the order: APOE4 ‐negative males > APOE4‐ positive males > APOE4 ‐negative females > APOE4‐ positive females (Begum et al .…”
Section: Apoe‐modulated Inflammation: Current Perspectivementioning
confidence: 97%
“…Indeed, Aβ‐specific CD4 + T‐cell activity follows the order: APOE4 ‐negative males > APOE4‐ positive males > APOE4 ‐negative females > APOE4‐ positive females (Begum et al . ). However, the significance of this T‐cell response for AD pathogenesis remains unclear.…”
Section: Apoe‐modulated Inflammation: Current Perspectivementioning
confidence: 97%
See 2 more Smart Citations
“…Several studies reported a positive correlation between the presence of one or more APOE-e4 alleles and neuritic plaques in AD [58,59]. Furthermore, research has shown that females carrying a copy of the APOE-e4 gene possess a 7-10% greater risk of developing Alzheimer's as compared with men [60,61]. Unlike AD, LBD, VaD, and PDD are more likely to affect men than women [62][63][64].…”
Section: Gender and Dementiamentioning
confidence: 99%